Develop drag estimation on hybrid electric vehicle (HEV) model using computational fluid dynamics (CFD) - Redzuan, Ahmad (2008)
Develop of drag estimation by using Computational Fluid Dynamics (CFD) on Hybrid Electric Vehicle (HEV) model was carried out on this project. The HEV model here means the Proton Iswara Hatchback body developed by researcher of Automotive Focus Group, Universiti Malaysia Pahang. To develop this HEV model, one of factor needs to consider and studied for giving better efficiency on the road is aerodynamics drag. Therefore, simulation of CFD and FEM have been the key features to aerodynamics drag studies in this project for the HEV model specifically is Proton Iswara Hatcback body. The objectives of this project are to estimate the drag of Proton Iswara Hatcback body at ranging speed between 40km/h to 110 km/h that designed by Computational Aided Design (CAD). The terminology to getting the drag estimation is by using input of CFD then export to FEM analysis to find the value of aerodynamics drag in terms of drag forces and drag coefficient. Besides that, CFD simulation results such as contour and trajectories plot also used to analyze the characteristics of streamlines flow or boundary layer that occurs on the body of this HEV model especially for the forebody, upperbody and rearbody. To achieve these objectives and rationalization made of project, aerodynamics studies, and study of CAD, CFD, and FEA engineering’s software needed to optimize the development of aerodynamic design on HEV model and to estimate the drag using CFD and FEA software as an alternative after experimental process. In this project also, a simple experiment was done to validate the CFD simulation analysis. The experiment known as Pressure Experiment that gives valuable results to compare with the simulation results as a validation process to this project.